The facile fabrication of g-C3N4 ultrathin nanosheets with higher specific surface areas for highly sensitive detection of trace cadmium. (July 2019) - Wang, Min; Fu, Rui; Jin, Chongyue; Li, Zhilin; Sun, Jie; Yu, Ping; You, Meiyan
Highlights: g-C3 N4 ultrathin nanosheets (NSCN) were synthesized via facile thermal polymerization. NSCN displayed higher surface reactive sites and better electrical conductivity. The limit of detection with NSCN-GC electrode can reach to 0.35 nM for Cd 2+ detection. The NSCN-GC electrode exhibited a good selectivity and repeatability in Cd 2+ detection. Abstract: To obtain a highly sensitive and selective electrochemical sensor for cadmium (Cd 2+ ) detection, graphitic carbon nitride (g-C3 N4 ) ultrathin nanosheets were synthesized via facile thermal polymerization taking melamine as raw materials and deionized water and acetic acid (AC) as bubble templates. The ultrathin g-C3 N4 nanosheet-modified glassy carbon (GC) electrode can detect metal ions through strong electrostatic interactions to metal ions and intercalation of the holes through square wave anodic stripping voltammetry (SWASV) measurements for Cd 2+ in aqueous solution. The calibration curves for Cd 2+ cover three linear ranges varying from 0.001 μM to 0.1 μM, 0.1 μM to 5 μM, and 5 μM to 18 μM. The limit of detection (LOD) is calculated to be 0.35 nM for Cd 2+, which is 76 times lower than the World Health Organization (WHO, 26.69 nM) standard for drinking water. In addition, the good repeatability and stability of the modified electrode is feasible for heavy metal detection in this study.